Research spillovers among European and North-American economics departments - Kalaitzidakis, Pantelis; Mamuneas, Theofanis P.; Savvides, Andreas; Stengos, Thanasis (My University, 2004)
In this paper, we investigate the determinants of research output by European economics departments. We use data from a survey we conducted on the various characteristics of these departments. We pay particular attention to spillovers from North America to Europe and measure these in terms of visiting arrangements between academic institutions across the Atlantic and formal training received by European faculty in North America. We find strong evidence that European economics departments with North-American links have higher research output.
Keywords: Educational economics; Productivity; Human capital